PENGARUH LATIHAN ZIG-ZAG RUN TERHADAP MENGGIRING BOLA SEKOLAH SEPAK BOLA (SSB) TOTAL FOOTBAL - Andi Bakhtiar Idris; Rachmat Hidayat; Rasyidah Jalil (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to evaluate the impact of zig-zag running practice on dribbling ability in total football schools in Palopo City. The method applied in this study is quantitative with an experimental design that includes pre-test and post-test in one experimental group. The research activity was carried out for a month in Gaspa, Palopo City, involving twenty athletes who were selected using purposive sampling techniques, namely based on criteria that were in accordance with the research objectives. The tools used include stopwatches, balls, cones, whistles, as well as books and pens, which are designed to assess dribbling skills through five key indicators: speed, strength, balance, and movement coordination. Data was collected by conducting skills tests, direct observations, and documentation. Data analysis was carried out through descriptive statistical tests, normality tests, homogeneity tests, and paired sample t-tests using SPSS software. The results showed a significant improvement in dribbling ability after zig-zag run exercises, with an average pre-test score of 24.7490 which increased to 22.6675 at the post-test. The results of the t-test gave a significance value of 0.000 (<0.05), which showed a significant impact of the zig-zag run exercise on dribbling ability at the Palopo total football school.